Bioactivities and Structure–Activity Relationships of Natural Tetrahydroanthraquinone Compounds: A Review - Feng, Shixiu; Wang, Weiyi (Frontiers in Pharmacology, 2020)
Tetrahydroanthraquinones are a kind of important microbial secondary metabolites with promising biological activities. Most of them were found in microorganisms, a few were derived from Chinese herbal medicine. In this review, aiming to provide basis for the further research and development of tetrahydroanthraquinone compounds, we summarized the physiological activities of natural tetrahydroanthraquinone compounds, including anti-cancer, anti-microbial and antidiabetic activities. The source, structure and action mechanisms of active tetrahydroanthraquinones are described in detail. Furthermore, this review firstly analyzed the structure-activity relationship of tetrahydroanthraquinones. Our study will serve as a valuable guideline for further research on the structural optimization, mechanism study and development of tetrahydroanthraquinone as novel drugs. Aiming to provide references for further studies and development of tetrahydroanthraquinone compounds.